Protein profile in cells exposed to non-thermal radiofrequency-field - Chai, Richie (2010)
The number of reports on the effects induced by radiofrequency (RF) electromagnetic fields radiation in various cellular systems is still increasing. Until now no satisfactory mechanism has been proposed to explain the biological effects of these RF fields. Some experiments were performed under isothermal conditions, have reported significant cellular changes after exposure to RF fields. According to some reports, it is widely accepted and assumed that certain class of protein has significant changes in abundance and concentration, which could initiate the changes in cell cycle reaction rates. Hence, this project focus on the in vitro study of changes in protein profile in cells after exposure to radiofrequency and evaluate the change in protein profile with relevance to the effect on human health. The experiment was conducted at 37°C. (±0.5°C) and the cell samples were subjected to 10, 40, 120 and 300 minutes of exposure under GSM 900MHz at 41V/m, a standard frequency appear in most of the telecommunication devices. LC/MS analysis was performed to identify the proteins which presented in cell samples. The protein concentration of radiated cells was compared against the sham samples. There were visible changes in relative abundance of Histone 2A and Histone 4, which can be linked to possible DNA damages. However, there was no evidence of changed in protein level especially in metabolic proteins. Thus, it is concluded that short term, non-thermal effect of radiofrequency exposure on cells is negligible.